2020
DOI: 10.1002/uog.21926
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of diffusion‐weighted magnetic resonance imaging of brain in fetal growth restriction: results of prospective multicenter study

Abstract: Objective To measure prospectively apparent diffusion coefficient (ADC) values between 28 and 32 weeks of gestation in different cerebral territories of fetuses with estimated fetal weight (EFW) ≤ 5th centile, and analyze their association with adverse perinatal outcome. Methods This was a prospective study involving six tertiary‐level perinatal centers. In the period 22 November 2016 to 11 September 2017, we included singleton, small‐for‐gestational‐age (SGA) fetuses with EFW ≤ 5th percentile, between 28 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
13
1
Order By: Relevance
“…DWI is applied regularly for the investigation of CNS abnormalities but remains a challenging technique 27,[42][43][44][45][46][47][48][49][50][51][52][53] . In our CMV cohort, we had a successful DWI acquisition in 85% of examinations, justifying routine implementation, but the possibility of failure should be discussed.…”
Section: Discussionmentioning
confidence: 99%
“…DWI is applied regularly for the investigation of CNS abnormalities but remains a challenging technique 27,[42][43][44][45][46][47][48][49][50][51][52][53] . In our CMV cohort, we had a successful DWI acquisition in 85% of examinations, justifying routine implementation, but the possibility of failure should be discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse perinatal outcomes were a composite measure of any of the following: neonatal death, hypoxic-ischemic encephalopathy, neonatal necrotizing enterocolitis, and pulmonary hemorrhage. 13…”
Section: Participants and Clinical Data Collectionmentioning
confidence: 99%
“…11 A prospective multicenter cohort study using DWI in the setting of FGR detected lower ADC values in the frontal white matter territory of fetuses and showed that this reduction in ADC was associated with adverse perinatal outcomes. 13 To our knowledge, no published study has examined the association of maternal PE or GH complicated by FGR with macrostructural and microstructural development of the fetal CC.…”
Section: Introductionmentioning
confidence: 99%
“…The application of gradients oriented in 3 planes in space using b-values between 0 and 700 s/mm 2 was chosen, since it is a part of many fetal imaging protocols, 14,[20][21][22] where b-values between 400 and 700 s/mm 2 are considered to demonstrate optimal contrast in the fetal brain. 20 The ADC maps were automatically calculated from the Siemens software.…”
Section: Mr Protocol and Post Processingmentioning
confidence: 99%
“…[10][11][12] Recent studies have found that ADC calculation is reproducible method for radiologists at different gestational ages. 13,14 ADC is equivalent to mean diffusivity (MD) and is a rotationally invariant quantity obtained from 3 orthogonal measurements for time-considerations. 15,16 MD is affected by the cellular density of a voxel, or many disease processes like edema, necrosis, or inflammation.…”
Section: Introductionmentioning
confidence: 99%